Lung cancer epidermal growth factor receptor mutations and radiotherapy response: A multicentre clinical study. (September 2021) - Hsu, Fred; Sit, Daegan; Pastuch, Andrea; Dingler, Angie; Atwal, Parmveer
Highlights: EGFR mutation status is not an independent predictor of response to palliative lung radiotherapy. TKIs remain important in local thoracic management even in patients who receive radiation. Acquired resistance to TKIs may be associated with cross-resistance to palliative radiotherapy. Abstract: Purpose: To examine the impact of epidermal growth factor receptor (EGFR) mutations on objective response to palliative lung radiotherapy in patients with metastatic non-small cell lung cancer (NSCLC). Materials and Methods: A multicentre retrospective study was conducted of patients with metastatic NSCLC diagnosed between March 2010 and June 2012 who received palliative radiotherapy to the chest. Patients included for study had baseline imaging and follow-up imaging 1–3 months after radiotherapy. The primary endpoint was 1–3 month local objective imaging response by the Response Evaluation Criteria in Solid Tumours (RECIST). Patients were divided into EGFR mutation positive (EGFR+) and EGFR wild type (WT) cohorts for analysis. Results: There were 121 patients for study inclusion: 89 (74%) were EGFR WT and 32 (26%) were EGFR+. The response rate between EGFR WT and EGFR+ cohorts was not significantly different (49 vs. 63%, p = 0.21). On multivariate analysis, initiation of a tyrosine kinase inhibitor (TKI) after radiotherapy was associated with a higher rate of response (OR: 5.07, 95%CI: 1.08–23.69, p = 0.039) but EGFR mutation status was not. For the EGFR+ cohort, patients with disease progression after initial management on a TKI had a worse response rate compared to patients who were TKI-naïve before starting radiotherapy (30 vs. 77%, p = 0.018). Local control was not statistically different between the EGFR cohorts. Conclusion: The EGFR mutation status alone was not an independent predictor of objective radiographic response to palliative thoracic radiotherapy. Acquired resistance to TKI therapy may be associated with disease cross-resistance to palliative radiotherapy.